Analisis Strategi Pemasaran Dengan Metode Bussiness Model Canvas (BMC) Melalui Pendekatan Bauran Pemasaran 4P (Product, Promotion, Price, Place) Pada Produk Pisau Stainless (Studi Kasus: UD. HS. Suharto) - Aura Balqis Putri Kurniawan, Vikha Indira Asri, Akh. Sokhibi (Universitas Muria Kudus, 2022)
UD.HS. Suharto is an iron industry located in Hadipolo village, Jekulo sub-district, Kudus district. This industry stands in an area with 300 other iron craftsmen, in recent months UD HS. Suharto received many complaints from consumers. The complaints come from products, prices, places, and promotions. So that consumers are more interested in knife products from other industries. Disadvantages of UD HS. Suharto did not make any improvements from the knife products which were still old-fashioned, the production sites were less strategic and difficult to find, plus the promotion was carried out only through word of mout. Methods to solve problems faced by UD HS. Suharto, it is necessary to do a marketing strategy analysis with the Business Model Canvas (BMC) and the Marketing Mix approach which refers to the results of the SWOT analysis using the IFE - EFE matrix so that it can evaluate the relationship between external and internal in order to increase sales. Based on the SWOT analysis, there are external and internal factors to increase sales of UD HS knife products. Suharto. The proposed marketing mix strategy to increase sales is to innovate in product design and promotion methods, strategic business locations, and determine affordable prices according to quality. Then the strategy that can be done based on BMC is by expanding the market segment, which is not only focusing on housewives or people who work as cooks, paying attention to the quality of goods produced, expanding sales in markets throughout Indonesia. Keywords: Marketing Strategy, Knives, Marketing Mix (Product, Price, Place, and Promotion), business model canvas (BMC)